Pembacaan Progresif Terhadap Fikih Keluarga (Kritik terhadap KHI dan RUU HTPA) - Sodik, Mochamad (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2012)
The formulation of several paragraphs in Compilation of Fikih (Kompilasi Hukum Islam/KHI) and Preliminary Ac t of Implemented Law of Religious Court (RUU HTPA) remain sustaining the subordination concept of women in family. The increase of wider access for women in education and public participation has promotes awareness on accomplishing woman's rights and children protection. This tendency requires progressive reading over conservative rationale that endured within fikih of Indonesian family. Conservative rationale is root deeply in fikih normativity rampart constructed by moslem theologian since 3rd century of Hijriyah. They likely to forbid the review of fikih teaching which had legitimized as final. Fikih is judge as conceptually definite. Moslems only requires to follow and implement the concept. Any critical review will be treated under suspicion, and frequently judge as ?apostate?. Progressive reading offers ijtihadi (serious thought) relevant to era dynamic, while remain stand on al-Quran. The reading over fikih of family is directed to gain gender equality and justice and protection over childrens rights, both boy and girls. The theoretical implication is constructing new paradigm that adapts contemporer human studies in reading humanize fikih. Whereas the practice implication is providing ethical-normative manual in implementing fikih that respects on dignity and honor each of all God creature.